الوسطية في العلاقات الخارجية كمحرك لاستعادة مكانة المسلمين الدولية: إسهامات "مالك بن نبي" نموذجا: (Moderation in Foreign Relations as an Engine for Restoring the International Status of Muslims: The Case Study of Malek Bennabi’s Contributions) - (Mohammed Salim Kelala), محمد سليم قلالة; (Salaheddine Youcef Aziez), صالح الدين يوسف عزيز (At-Tajdid - Intellectual Refereed Journal, 2021)
Abstract In the field of international relation especially considering the current developments of world order; the Muslim world needs to assert its point of view. In order to do so, the Muslim world should review their contribution in this regard, starting from the characteristics of their historical experience and revive it with reality. This paper seeks to provide a brief outcome of the Muslims contribution to the theory of international relations and their criticism of Western perception of it from three angles (Their European foundations, their double vision, the conflicting values they adopt). The paper also aims to provide the view of some Muslim scholars in this aspect and to highlight the supreme value of justice that control their external perspective. It brings to light the relationship of this value to the value of moderation in international relation and how it is manifested through its association with the Muslim doctrine and the principles of interest and the fulfillment of covenants. Finally, the paper provides an example of moderation in international relation through the contributions of Malek Bennabi in building the relationship between the aspects of power and survival and the extent of the ability of Muslims to find a unified concept of humanity in the future. Keywords: International Islamic Relations, International Islamic Values, International moderation, Malek Bennabi, International Political Values. Clash of Civilization.